2004
DOI: 10.1111/j.1346-8138.2004.tb00530.x
|View full text |Cite
|
Sign up to set email alerts
|

Psychological Disturbances in Indian Children with Atopic Eczema

Abstract: Although the link between atopic dermatitis (AD) and emotional disturbance is well known, there have been only a few studies assessing the extent of these disturbances in affected children and the problems experienced by their parents. Furthermore, these studies are mostly from western countries, where atopic dermatitis is seen in a more severe form than in India. The purpose of this study was to determine whether there is an excess of psychological disorders in Indian children with AD as compared to healthy c… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
7
0
1

Year Published

2006
2006
2018
2018

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 18 publications
(8 citation statements)
references
References 12 publications
0
7
0
1
Order By: Relevance
“…Studies were grouped into 3 categories according to the end points: (1) depression, (2) anxiety, and 3suicidal ideation. In the first category, 42 studies were included 7,9,10,[13][14][15][16][17][18][19][20][21][22][23][24][25][26][27][28][29][30][34][35][36][37][38][39][40][41][42][44][45][46][47][48][49][50][51][52]54 ; in the second category, 44 studies were included 7,10,[13][14][15][16][17][18][19][23]<...>…”
Section: Data Extractionmentioning
confidence: 99%
See 2 more Smart Citations
“…Studies were grouped into 3 categories according to the end points: (1) depression, (2) anxiety, and 3suicidal ideation. In the first category, 42 studies were included 7,9,10,[13][14][15][16][17][18][19][20][21][22][23][24][25][26][27][28][29][30][34][35][36][37][38][39][40][41][42][44][45][46][47][48][49][50][51][52]54 ; in the second category, 44 studies were included 7,10,[13][14][15][16][17][18][19][23]<...>…”
Section: Data Extractionmentioning
confidence: 99%
“…23,25 A total of 19 studies were included in the qualitative analysis. [34][35][36][37][38][39][40][41][42][44][45][46][47][48][49][50][51][52]54 Most either found an association between patients with AD and depression 34,[36][37][38][39][40]44,[46][47][48][49][50] or reported a higher mean score 41,51,52,54 according to the assessment tool used to diagnose depression. A Korean cross-sectional study found a positive association between childhood AD and depression (N = 3192 [P = .0003]).…”
Section: Ad and Depressionmentioning
confidence: 99%
See 1 more Smart Citation
“…[29] In a small matched case-control study involving children between 3 and 9 years of age, it was observed that AD children were more prone for low intelligence with behavior disorders and conduct disorders. This was notwithstanding the milder nature of the disease in Indian patients.…”
Section: Clinical Features Of Admentioning
confidence: 99%
“…There was no difference in the degree of social support experienced by the eczema families in this study. A small study from India ( n = 22) found that an increased number of mothers of affected children, 59%, were submissive when compared to 10% in the control group ( p < 0.01) [ 53 ] .…”
Section: Psychological Impairment In Children With Eczema and Their Pmentioning
confidence: 99%